IMPLEMENTASI PENDEKATAN STEAM DALAM PEMBELAJARAN ANAK USIA DINI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in early childhood education at TK Negeri Pembina Cibeureum. A qualitative descriptive methodology was employed, involving teachers and 17 students from Group B, categorized into four learning groups. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing. The findings reveal that the STEAM approach was operationalized through simple science experiments, specifically a volcanic eruption simulation. This activity successfully integrated the five STEAM components into a contextual and meaningful learning experience. While most children demonstrated high levels of enthusiasm, curiosity, and active participation in group work, their communicative engagement—particularly in posing questions and articulating opinions—remained limited to a few individuals. Furthermore, the predominance of teacher-centered instruction and inadequate facilities were identified as primary constraints to optimizing STEAM implementation. The study concludes that the STEAM approach holds significant potential for enhancing the quality of early childhood education by fostering an active, creative, and meaningful learning environment. Consequently, improving teacher competencies and upgrading educational facilities are essential to ensure a more effective and robust application of STEAM.